Dietary iron intake and anemia: food frequency questionnaire in patients with hereditary hemorrhagic telangiectasia - Federica Cavalcoli; Alberto Gandini; Irene Aglaia Matelloni; Francesca Catalano; Saverio Alicante; Guido Manfredi; Gianfranco Brambilla; Fernanda Menozzi; Federica Perolini; Egon Costi; Roberto Bertè; Elisabetta Buscarini (Orphanet Journal of Rare Diseases, 2020)
Abstract Background Hereditary hemorrhagic telangiectasia (HHT) is a multisystemic inherited vascular disease characterized by a heterogeneous clinical presentation and prognosis. Dietary evaluation is relevant in HHT patients to provide adequate iron and nutrient intake. Additionally, different dietary items have been reported to precipitate epistaxis in this setting. Our primary aim was to investigate the dietary habits of HHT patients through a food-frequency questionnaire (FFQ) to evaluate the presence of precipitants and/or protective factors for epistaxis and the occurrence of possible dietary modifications. The secondary aims were to evaluate the nutritional intake of iron in HHT patients and the self-reported effect of iron treatments on epistaxis. From April 2018 to October 2018, a 138-item FFQ was provided to HHT patients followed up at the HHT Referral Center of Crema Maggiore Hospital. The relationship between food items and epistaxis was ascertained on a separate form. Daily iron intake was calculated to establish the mean iron content of food items reported in the FFQ. Results One hundred forty-nine questionnaires were evaluated [72 females, median age 54 years (12–76). Overall, 26 (18%) patients reported dietary items that improved epistaxis (mostly blueberries and red fruits, green vegetables and legumes), while 38 (26%) reported some dietary items that exacerbated epistaxis (spices, chocolate, alcohol, strawberries and ginger). Dietary modifications were reported in up to 58% of cases. In HHT patients, the mean daily iron intake was 8.46 ± 2.78 mg, and no differences were observed in the iron intake of patients reporting a diet modification and those who did not. Conclusions In the comprehensive management of HHT a healthy and balanced diet, with increased consumption of dietary items with a high iron content, should be encouraged.